Reactive Ating Soil Ripping Treatments for Runoff And Erosion Control in the Southwestern Us - Aldon, Earl F (Annals of Arid Zone, 2016)
Soil ripping is an effective, but temporary. measure to control runoff and erosion on semi-arid watersheds. Its effectiveness, normally 3 to 5 years in the southwestern US, depends on storm amounts and intensities. Re-ripping previously treated areas may be a low-cost way to extend treatment effectiveness until vegetation can be established. In this study, opening old rips that were sealed over with sediment was as effective in controlling runoff as ripping between old rips. Re-ripping by either method reduced runoff by two-thirds compared with untreated check plots. Ripping must be done carefully to avoid subterranean channel formation (erosion by soil piping).